2015
DOI: 10.5089/9781484308691.001
|View full text |Cite
|
Sign up to set email alerts
|

IMF Lending and Banking Crises

Abstract: In this paper we look at the effect of International Monetary Fund (IMF) lending programs on banking crises in a large sample of developing countries, over the period 1965-2010. The endogeneity of the Fund intervention is addressed by adopting an instrumental variable (IV) strategy, in which the degree of political similarity between IMF borrowers and the G-7 is taken as an instrument for the likelihood of a country signing an IMF lending arrangement. Controlling for the standard determinants of banking crises… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 87 publications
0
11
0
Order By: Relevance
“…This is supported by Demirgüҫ-Kunt and Detragiache Papi et al (2013) found that the ratio of the money supply very positive effect on the financial and banking crisis, bad loans will rise due to the falling value of the currency that is, when the nonperforming Loan (NPL) the higher the risk of default customers also will increase. This condition will worsen the banking performance.…”
Section: Determinant Of Banking Crisismentioning
confidence: 74%
“…This is supported by Demirgüҫ-Kunt and Detragiache Papi et al (2013) found that the ratio of the money supply very positive effect on the financial and banking crisis, bad loans will rise due to the falling value of the currency that is, when the nonperforming Loan (NPL) the higher the risk of default customers also will increase. This condition will worsen the banking performance.…”
Section: Determinant Of Banking Crisismentioning
confidence: 74%
“…But such a strategy has two limitations: (i) it does not control for unobservable factors and unaccounted observable characteristics, and (ii) it may be subject to inconsistent estimates if collinearity problems prevail (Puhani 2002 ). 2 Finally, given the above evidence from Eichengreen et al ( 2006 ), Dreher and Walter ( 2010 ), and Papi et al ( 2015 ), a natural question emerges. Why should IMF involvement lower the likelihood of sudden stops, currency crises and banking crises, while increasing the risk of sovereign defaults?…”
Section: Literature Reviewmentioning
confidence: 98%
“…The author stresses that his result cannot be attributed to an endogeneity bias or a lack of compliance with IMF conditionality, as his empirical specification explains simultaneously sovereign defaults and program participation. Apart from Jorra ( 2012 ), previous empirical studies analyzing the direct association between bailouts in the context of IMF lending programs and crises focus on three types of crises: sudden stops, currency crises, and banking crises (Eichengreen et al 2006 ; Dreher and Walter 2010 ; Papi et al 2015 ). Eichengreen et al ( 2006 ) examine the impact of IMF-supported programs on the incidence of sudden stops in capital flows.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“… PSM was used for assessing the effects of capital account liberalization (Glick, Guo, and Hutchinson ), inflation targeting adoption (Lin and Ye ; Lin ; Minea and Tapsoba ), real exchange rate appreciation (Bussière, Lopez, and Tille ), IMF‐supported programs on development aid and banking crises (Gündüz and Crystallin ; Papi, Presbitero, and Zazzaro ), and policy response to crises (Forbes and Klein ), among others. See also Caliendo and Kopeinig () for a detailed discussion regarding the implementation of PSM.…”
mentioning
confidence: 99%